Evolutionary Changes in the Interaction of miRNA With mRNA of Candidate Genes for Parkinson’s Disease - Kamenova, Saltanat; Aralbayeva, Assel; Kondybayeva, Aida; Akimniyazova, Aigul; Pyrkova, Anna; Ivashchenko, Anatoliy (Frontiers in Genetics, 2021)
Parkinson's disease (PD) exhibits the second-highest rate of mortality among neurodegenerative diseases. PD is difficult to diagnose and treat due to its polygenic nature. In recent years, numerous studies have established a correlation between this disease and miRNA expression; however, it remains necessary to determine the quantitative characteristics of the interactions between miRNAs and their target genes. In this study, using novel bioinformatics approaches, the quantitative characteristics of the interactions between miRNAs and the mRNAs of candidate PD genes were established. Of the 6756 miRNAs studied, more than one hundred efficiently bound to mRNA of 61 candidate PD genes. The miRNA binding sites were located in the 5′-untranslated region (5′UTR), coding sequence (CDS) and 3′-untranslated region (3′UTR) of the mRNAs. In the mRNAs of many genes, the locations of miRNA binding sites with overlapping nucleotide sequences (clusters) were identified. Such clusters substantially reduced the proportion of nucleotide sequences of miRNA binding sites in the 5′UTRs, CDSs, and 3′UTRs. The organization of miRNA binding sites into clusters leads to competition among miRNAs to bind mRNAs. Differences in the binding characteristics of miRNAs to the mRNAs of genes expressed at different rates were identified. Single miRNA binding sites, polysites for the binding for one miRNA, and multiple binding sites for two or more miRNAs in one mRNA were identified. Evolutionary changes in the binding sites of miRNAs and their clusters in 5'UTRs, CDSs and 3'UTRs of mRNA of orthologous candidate PD genes were established. Based on the quantitative characteristics of the interactions between miRNAs and mRNAs candidate PD genes, several associations recommended as markers for the diagnosis of PD.